Utilization Of Digital Marketing and Product Innovation In Improving Msme Marketing Performance In Talun District - Salsabilla, Meisya; Aulia, Dyta; Maulany, Soesanty (Ridwan Institute, 2024)
The purpose of this study is to examine the influence of digital marketing and product innovation on the marketing performance of MSMEs in Talun District. This study used quantitative methods. The population in this study is culinary MSME business actors in Talun District, with a sample of 100 people. The data collection technique in this study used a questionnaire with a measurement scale using the Likert scale. The data analysis technique used in this study is multiple linear regression analysis. The results of this study show that partially digital marketing and product innovation have a positive and significant influence on marketing performance, and simultaneously digital marketing and product innovation have a positive and significant effect on market performance.